'Blessed are the young, for they shall inherit the national debt': Solidarity between generations in the Irish crisis. (August 2014) - Carney, Gemma M.; Scharf, Thomas; Timonen, Virpi; Conlon, Catherine
Ireland has gained a reputation for peaceable acceptance of austerity following a European Union/International Monetary Fund bailout in 2010. While proponents of austerity praise Ireland's stoicism, critics of global capitalism argue that individuals and families are paying for mistakes made by elites. However, little is known about the strategies people adopt to cope with cutbacks to welfare entitlements. Drawing on a study of solidarity between generations living in Ireland in 2011–12, this article explores the lived experience of economic crisis and austerity. One hundred interviews with people of all ages and socio-economic backgrounds are analysed using constructivist grounded theory. Data show how austerity impacts differentially according to socio-economic status. While solidarity between generations leads to re-distribution of resources within families, providing some security for people with access to family resources, it reinforces inequality at societal level. We conclude that reliance on family promotes 'coping' rather than 'protesting' responses to austerity.